Determining the Role of Urine Investigations in Urology Practice - Musa, Muhammad Ujudud (New Horizons in Medicine and Medical Research Vol. 12, 2022)
Urine as a by-product of the glomeruli ultra-filtrations has a lot of stories to tell about the urinary system, therefore a urologist being concerned with the surgical aspect of the genitourinary system will extract many important and useful information through studying the urine. The art of urine examination dated back to antiquates were the physical properties as well as the chemical properties where assessed. the term uroscopy was coined to describe the using urine as the primary diagnostic tool of many disease conditions and was an extension of physical examination in arriving at the diagnosis of the pathology, Uroscopy was regarded as the mirror of medical practice for a long time. whereby a liquid and simple window physicians used to forecast and, in most cases, accurately determines the disease process, and consequently several Urological and Nephrological and Physiologic theories were postulated from urine examination. Then the importance of urinary diagnosis became exaggerated, and increasingly complex, until physicians required only the presence of urine, not patients, to diagnose disease. Uroscopy then escaped medical control, becoming first a home health aid and then a tool of uneducated practitioners. Thomas Brian led a medical rebellion against all uses of uroscopy and published a book that devastated uroscopy. Urine examination is one of the important armamentariums in the practice of urology and it is a fundamental test that is usually carried out for urology patients, it can be as simple as dipstick analysis to a complex hormonal assay. Urine examination is done worldwide as an extension of physical examination which provides a lot of information about the pathology, and both physical and chemical analysis of urine are highly informative. There are several types of urine investigations, some of which include urinalysis, urine microscopy culture and sensitivity, urine microscopy for ova or cyst of parasites, urine cytology, urine tumour antigens assays, urine hormonal assays, urine toxicology, urine quantitative measurement and urine acid fast bacilli. Uses of urine examinations in urology could be diagnostic, such as renal function test, evaluation of haematuria, stone diseases, urinary tract infections, urologic cancers and infertility or monitoring and for prognosis. Uses of urine investigations in practice of urology cannot be over emphasized as it has many revealing information of the physiology and pathology of urologic organs. Objectives of the study is to highlight the relevant role investigations of urine plays in the practice of urology from ancient times to modern day medicine.